2014
DOI: 10.3109/09546634.2013.879094
|View full text |Cite
|
Sign up to set email alerts
|

Plaque-based sub-blistering dosimetry: Reaching PASI-75 after two treatments with 308-nm excimer laser in a generalized psoriasis patient

Abstract: This case demonstrates using a more aggressive dosing protocol determined by plaque testing is well-tolerated and can lead to excellent clearance with minimal side effects and comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Studies have revealed that 308 nm excimer laser can significantly reduce the level of TnF-α in lesions (101), thereby promoting Mc function. Various studies reported that the expression of il-4, TnF-α and other inflammatory cytokines was downregulated after topical application of tacrolimus in lesions of vitiligo (102,103).…”
Section: Post-inflammatory Hyperpigmentations and Hypopigmentations Cmentioning
confidence: 99%
“…Studies have revealed that 308 nm excimer laser can significantly reduce the level of TnF-α in lesions (101), thereby promoting Mc function. Various studies reported that the expression of il-4, TnF-α and other inflammatory cytokines was downregulated after topical application of tacrolimus in lesions of vitiligo (102,103).…”
Section: Post-inflammatory Hyperpigmentations and Hypopigmentations Cmentioning
confidence: 99%
“…In a single-center pilot study, patients with greater than 10% but less than 30% body surface area involvement (moderate to severe psoriasis) were treated with excimer laser twice weekly for 12 weeks for a total of 24 treatment sessions. Fifty-four percent achieved PASI-75 and 83% achieved PASI-50, which was maintained without further treatment for 6 months 32 . However, the downside to treating moderate to severe psoriasis is the long duration required per session to treat a large body surface area, which may not be feasible in many dermatology office settings.…”
Section: Recent Advancesmentioning
confidence: 88%
“…It typically takes 5 to 10 treatments of incremental dose increase just to reach the ideal maximum dose of the plaque. A recent study has attempted to develop a new dosing protocol called “plaque-based sub-blistering dosimetry”, in which the patient’s psoriatic plaque, rather than uninvolved skin, is tested with incrementally increasing doses to determine the dose at which blistering is observed 32 . The patients then are treated just below that dose.…”
Section: Recent Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Furthermore, the excimer laser has the ability to target difficult to reach areas and administer site-specific dosing. 16 Also, it can operate with the ability to change the energy level (in millijoules) delivered during treatment. Few adverse reactions have been reported, and they are consistent with adverse reactions associated with other forms of phototherapy including erythema, blistering, hyperpigmentation, and hypopigmentation ( Figure 3 ).…”
Section: Safetymentioning
confidence: 99%